Human-machine Dynamics in Local Digital Governance: Evidence from North Kalimantan’s SPBE - Zain, Ilham; Yunus, Muhammad; Syahribulan, ‎; Ibrahim, Muhammad Akmal; Haning, Mohamad Tahir; Hans, Amril (KnE Social Sciences, 2025)
One of the efforts to improve the quality of public services is the implementation of the electronic-based government system (SPBE). However, in its implementation, various regions experienced different obstacles, including North Kalimantan Province. This obstacle is primarily related to the capacity of employees in the government and the community in adapting to and adopting technology, which tends to indicate that there is still resistance to the use of digital systems in public service processes. The lack of human resources with technological capacity also remains an obstacle in the implementation of the SPBE in North Kalimantan. This situation causes government agencies to prefer collaborating with third parties for the preparation and development of related applications. In addition, the quality of technological infrastructure is also not yet adequate, with only 65% of the areas in North Kalimantan Province having stable internet access.